Echomorphologic and Histopathologic Characteristics of Unstable Carotid Plaques - Tegos, Thomas J.; Sohail, Muhammed; Sabetai, Michael M.; Robless, Peter; Akbar, Nuzhat; Pare, Gary; Stansby, Gerard; Nicolaides, Andrew N. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Our hypothesis was that the carotid plaques associated with retinal and cerebrovascular symptomatology and asymptomatic presentation may be differ from each other. The aim of this study was to identify the sonographic and histopathologic characteristics of plaques that corresponded to these three clinical manifestations.METHODS: The echo process involved duplex preoperative imaging of 71 plaques (67 patients, 21 plaques were associated with retinal, 25 with cerebrovascular symptoms, and 25 were asymptomatic), which was performed in a longitudinal fashion. Appropriate frames were captured and digitized via S-video signal in a computer and digitized sonograms were normalized by two echo-anatomic reference points: the gray scale median (GSM) of the blood and that of the adventitia. The GSM of the plaques was evaluated to distinguish dark (low-GSM) from bright (high-GSM) plaques. Subsequent to endarterectomy, the plaques were sectioned transversely, and a slice at the level of the largest plaque area was examined for the relative size of necrotic core and presence of calcification and hemorrhage.RESULTS: Retinal symptomatology was associated with a hypoechoic plaque appearance (median GSM: 0), asymptomatic status with a hyperechoic plaque appearance (median GSM: 34), and cerebrovascular symptomatology with an intermediate plaque appearance (median GSM: 16) (P = .001). The histopathologic characteristics did not disclose differences between the three clinical groups. The hypoechoic plaque appearance was associated only with the presence of hemorrhage (median GSM for the hemorrhagic plaques, 6, and for the non-hemorrhagic ones, 20 [P = .04]). The relative necrotic core size and the presence of calcification did not show any echomorphologic predilection.CONCLUSION: Our results showed that distinct echomorphologic characteristics of plaques were associated with retinal and cerebrovascular symptomatology and asymptomatic status. Histopathologically, only the presence of hemorrhage proved to have an echomorphologic predilection.